Molecular weight abnormalities of the CTCF transcription factor: CTCF migrates aberrantly in SDS-PAGE and the size of the expressed protein is affected by the UTRs and sequences within the coding region of the CTCF gene. - Klenova, E M (1997)
CTCF belongs to the Zn finger transcription factors family and binds to the promoter region of c-myc. CTCF is highly conserved between species, ubiquitous and localised in nuclei. The endogenous CTCF migrates as a 130 kDa (CTCF-130) protein on SDS-PAGE, however, the open reading frame (ORF) of the CTCF cDNA encodes only a 82 kDa protein (CTCF-82). In the present study we investigate this phenomenon and show with mass-spectra analysis that this occurs due to aberrant mobility of the CTCF protein. Another paradox is that our original cDNA, composed of the ORF and 3'-untranslated region (3'-UTR), produces a protein with the apparent molecular weight of 70 kDa (CTCF-70). This paradox has been found to be an effect of the UTRs and sequences within the coding region of the CTCF gene resulting in C-terminal truncation of CTCF-130. The potential attenuator has been identified and point-mutated. This restored the electrophoretic mobility of the CTCF protein to 130 kDa. CTCF-70, the aberrantly migrating CTCF N-terminus per se, is also detected in some cell types and therefore may have some biological implications. In particular, CTCF-70 interferes with CTCF-130 normal function, enhancing transactivation induced by CTCF-130 in COS6 cells. The mechanism of CTCF-70 action and other possible functions of CTCF-70 are discussed.